Pengaruh Self-Confidence Terhadap Kemampuan Komunikasi Matematis Siswa Kelas VIII SMPN 5 Mataram Tahun Ajaran 2024/2025 - Widya, Eka; Syahrul Azmi; Ni Made Intan Kertiyani (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Self-confidence is considered a key psychological factor in enhancing students' ability to communicate mathematical ideas effectively. However, few studies have explored this relationship in the context of lower secondary education. This study aims to investigate the effect of self-confidence on the mathematical communication skills of eighth-grade students at SMP Negeri 5 Mataram during the 2024/2025 academic year. A quantitative approach with an ex post facto design was employed. A purposive sample of 29 students was selected, and data were collected using a self-confidence questionnaire and a mathematical communication skills test on the topic of systems of linear equations in two variables. The data were analyzed using descriptive statistics and simple linear regression. With the regression equation, the correlation coefficient, and the coefficient of determination. The results indicate that self-confidence has a significant positive effect on students' mathematical communication skills. These findings underscore the importance of cultivating students' self-confidence to support their development of mathematical communication skills.